Synergistic local toughening of high performance epoxy-matrix composites using blended block copolymer-thermoplastic thin films. (December 2016) - Bahrami, Amir; Cordenier, François; Van Velthem, Pascal; Ballout, Wael; Pardoen, Thomas; Nysten, Bernard; Bailly, Christian
Abstract: A new block copolymer-thermoplastic dual toughening concept for high performance RTM6 epoxy matrix composites is elaborated through a comprehensive microstructural study of well-defined model systems. A blend of phenoxy and MAM (copolymer of poly(methyl methacrylate) and poly(butyl acrylate)) increases the toughness of the corresponding carbon fiber reinforced composite by 125%, a five-fold synergistic improvement over the situation where the tougheners are used alone at the same total concentration. Selective intercalation of blended toughener thin films in the preform gives rise to a diffusion-induced composition gradient during the RTM process, which generates a morphology gradient upon curing. The observed microstructures results from MAM self-assembly in the miscible mixture of phenoxy and the epoxy resin precursor, followed by reaction induced phase separation, forming wormlike micelles, interconnected micelles and co-continuous morphologies. The resulting microstructures activate different toughening mechanisms responsible for the observed synergy.